Screen house sebagai sarana untuk meningkatkan jiwa enterpreunership warga dalam pengembangan tanaman pangan dan hortikultura - Heristama Putra; Ryan Putranda Kristianto; Odo Grean Kaesar Putra Wardhana; Yohana Christela Oktaviani (STAI Auliaurrasyidin Tembilahan, 2025)
Cultivating an entrepreneurial spirit within the community is essential for business resilience. This can be fostered through activities such as independent food and horticultural production. By learning cultivation techniques, community members can reduce their dependence on purchased food. The primary challenge being addressed is food security, particularly the threat of price inflation and scarcity of raw materials during extended dry seasons. Effective seed management is a crucial strategy to overcome this issue. However, this strategy requires adequate facilities. To address this need, a community service initiative was implemented using an assistance method. This project proposes the establishment of a screen house in the Babatan Pilang RT 002/RW 005 housing complex. This facility aims to simplify the seed sowing process for residents before transplantation to open fields, thereby supporting sustainable local cultivation.